Kejadian Postoperative Nausea and Vomiting pada Pasien Paca Operasi dengan Anestesi Spinal dan General - Zeda Ardeana Estiningsih; Danang Tri Yudono; Dwi Novitasari; Awal Tunis Yantoro (Universitas Malahayati Lampung, 2026)
ABSTRACT Post Operative Nausea and Vomiting (PONV) is a common postoperative complication that can decrease patient comfort, hinder recovery, and prolong hospitalization. The incidence of PONV is influenced by various factors, one of which is the type of anesthesia used. Spinal and general anesthesia differ in their mechanisms of action and physiological effects on the central nervous and gastrointestinal systems, which may contribute to the occurrence of nausea and vomiting after surgery. This study aimed to describe the incidence of PONV based on the type of anesthesia among postoperative patients at RSUD Kajen. This research employed a quantitative design with a descriptive observational approach. The population consisted of all patients who underwent surgical procedures using either spinal or general anesthesia. The sample size of this study consisted of 79 respondents, determined using the Slovin formula, and the respondents were subsequently selected through purposive sampling based on the predetermined inclusion and exclusion criteria. Data were collected through direct observation and medical record review, including anesthesia type, patient characteristics (age, gender, and type of surgery), as well as the incidence and severity of PONV. Data were analyzed using univariate analysis to describe the frequency distribution of each research variable. Most respondents received spinal anesthesia (60.8%) and were female (65.8%). The majority of patients did not experience PONV (74.7%), while severe PONV was more commonly observed in patients who received general anesthesia (6.5%) compared to those who received spinal anesthesia. These findings indicate that the type of anesthesia may influence the incidence of PONV in postoperative patients. PONV was more frequently found in patients receiving general anesthesia than in those receiving spinal anesthesia. Appropriate selection of anesthesia type and administration of prophylactic antiemetic therapy can help reduce the incidence of PONV and improve postoperative patient comfort. Keywords: General Anesthesia, PONV, Postoperative, Spinal Anesthesia. ABSTRAK Post Operative Nausea and Vomiting (PONV) merupakan komplikasi pasca pembedahan yang sering terjadi yang dapat menurunkan kenyamanan pasien, menghambat pemulihan, serta memperpanjang rawat inap. Insidensi PONV dipengaruhi oleh berbagai faktor, salah satunya jenis anestesi yang digunakan. Anestesi spinal dan anestesi general memiliki mekanisme kerja serta efek fisiologis yang berbeda terhadap system saraf pusat dan system gastrointestinal yang dapat memengaruhi terjadinya mual muntah pasca operasi. Tujuan umum dari penelitian ini yaitu mengetahui gambaran kejadian PONV berdasarkan jenis anestesi pada pasien post operasi di RSUD Kajen. Penelitian ini menggunakan desain kuantitatif dengan pendekatan deskriptif observasional. Populasi penelitian adalah seluruh pasien yang menjalani tindakan pembedahan dengan anestesi spinal maupun general. Jumlah sampel penelitian ditetapkan sebanyak 79 responden berdasarkan hasil perhitungan menggunakan rumus Slovin, selanjutnya responden dipilih dengan Teknik purposive sampling sesuai kriteria inklusi dan eksklusi yang telah ditentukan. Data dikumpulkan melalui observasi langsung dan telaah rekam medis, mencakup jenis anestesi, karakteristik pasien (jenis kelamin, riwayat merokok, usia, durasi pembedahan, jenis pembedahan, lama puasa), serta kejadian dan derajat PONV. Data dianalisis menggunakan analisis univariat untuk menggambarkan distribusi frekuensi tiap variable penelitian. Sebagian besar responden menggunakan anestesi spinal (60,8%) dan berjenis kelamin perempuan (65,%). Mayoritas pasien tidak mengalami PONV (74,7%), sedangkan PONV berat lebih sering ditemukan pada pasien yang mendapatkan anestesi general (6,5%) dibandingkan anestesi spinal. Temuan ini menunjukkan bahwa jenis anestesi berpotensi memengaruhi kejadian PONV pada pasien post operasi. Kejadian PONV lebih banyak ditemukan pada pasien dengan anestesi general dibandingkan anestesi spinal. Pemilihan jenis anestesi yang tepat dan pemberian terapi antiemetik profilaksis dapat membantu menurunkan angka kejadian PONV. Kata Kunci: Anestesi General, Anestesi Spinal, PONV, Postoperative.